The Covenant - Michener, James A. (London Corgi Books, 1981)
A historical novel covering over 15,000 years of history in South Africa and which focuses on three principal families who settled in the region throughout the centuries. The family of Nxumalo; the van Doorns, a Dutch family; and the Saltwoods of England.
Keywords: South Africa -- Fiction